Parasites and Wildlife - Calero-Bernal, Rafael; García-Bocanegra, Ignacio (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on field studies aimed at unraveling the complex networks created by interactions between parasites and hosts in a given ecosystem. Since most transboundary diseases have been propagated from the wilderness to anthropized areas, societies are increasingly concerned about the relevance of wildlife as it pertains to global health. In this respect, research on parasites that may affect the biology and population equilibrium of wildlife is of major interest, especially when a One Health perspective is considered. The studies compiled in the present Special Issue fall within several areas of interest, such as epidemiology, diagnosis, emerging zoonoses, food safety, conservation issues, parasite-host interactions, and the pathology of infections caused by parasites in wild host species.